The contrasting views on the development of Arabic grammar: a brief ananlysis - Yaacob, Solehah@Nik Najah Fadilah (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
There have been debates and discussions on the influence of Greek on Arabic. Modern historians such as Ahmad Amīn in his book Öuha al-Islām(1969) say that Hunain bin Ishāķ(260H/873A.D) ( J.Ruska,1980:134) went to Rome to learn Greek and then came back to Başrah to learn from Khalīl (Amīn Ahmād, 1978:v.1:313). This idea is strongly supported by Mustafa NaÐīf when he states that Khalīl was visited by Hunain to study Arabic (1978:vol.1:313). Modern historians believe that time were influenced by Greek civilization such as Bustānī, a learned man who was very competent in Greek, and Khalīl, who was influenced by Aristotle`s ideas especially on the concept of cause and effect ( Mahdī al-Makhzūmī,1986:68). Muşţafā Şadiq Raf‘ie says that al-harakāt in Arabic did not originate from Arabia but from Syria when it was governed by the Romans, who put some small harakāt when they read the Bible (Karl Brokelman, 1968:vol.1:105).